Biocatalysis for the production of pharmaceutical intermediates statin precursors - Švarc, Anera; Skendrović, Dino; Vrsalović Presečki, Ana (2019)
The application of enzymes in chemical synthesis, due to the recent advances, has a strong impact in multiple industries, especially the pharmaceutical industry. Namely, the use of enzymes shows remarkable advantages over classical chemical catalysis and therefore it is considered a ‘green’ solution. By using novel techniques, it is possible to tailor the enzymes to adapt them for a given process. Today, several pharmaceutical companies are successfully producing valuable precursors for the production of active pharmaceutical ingredients using enzymes, some of them being statin precursors. Statins are hypolipidemics, drugs used for the prevention of cardiovascular diseases and lowering cholesterol concentration in blood. Due to challenges in the chemical synthesis of statin intermediates, the production of statin intermediates using enzyme-catalysed reactions shows some notable advantages. Therefore, research and development laboratories, combined with reaction engineering techniques, have shifted their focus towards applying biochemical catalysis for the production of statin intermediates.
Napredak tehnologije usko je vezan uz primjenu enzima u kemijskoj sintezi. Biokataliza ima velik utjecaj na različite industrije a među njima se posebno ističe farmaceutska industrija. Primjena enzima pokazuje značajne prednosti u usporedbi s tehnikama klasične kemijske sinteze te se smatra i ‘zelenim’ rješenjem. Primjenjujući nove dostupne tehnike i tehnologije, enzime je moguće u potpunosti prilagoditi zahtjevima određenog procesa. Danas je poznato nekoliko farmaceutskih tvrtki koje uz pomoć enzima uspješno proizvode vrijedne intermedijare za proizvodnju aktivnih farmaceutskih spojeva, a u njih se ubrajaju i prekursori statina. Statini su hipolipidemici, lijekovi koji se upotrebljavaju za prevenciju kardiovaskularnih bolesti te za snižavanje koncentracije kolesterola u krvi. Metoda klasične kemijske sinteze intermedijara statina vrlo je zahtjevna te stoga njihova proizvodnja primjenom enzimski kataliziranih reakcija ima značajne prednosti. Iz tog razloga za proizvodnju intermedijara statina istraživanje i razvoj uz primjenu reakcijskog inženjerstva sve se više usmjeravaju prema primjeni biokatalize.
Bibliografija: 89 jed.
Summary ; Sažetak.
Keywords: Biokataliza -- Enzimi -- Statini -- Intermedijari -- Farmaceutska industrija